Tanah Pertemuan Raja: Sejarah Pernaskahan Kerinci 1370-1819 M - Kozok, Uli (Jumantara: Jurnal Manuskrip Nusantara, 2024)
In the last 500 years, the Kerinci valley, while enjoying de facto independence, always acknowledged the sovereignty of either Jambi, Indrapura, or Minangkabau. This article examines manuscripts sent by the suzerains of the three kingdoms to the headmen (Depati) of Kerinci and puts them into a historical perspective with particular emphasis on the social and economical impact brought upon the society by the arrival of Islam and colonialism in central Sumatra suggesting that the legal system of Malayu-Jambi essentially remained the same while the fundamental changes in the field of politics and economy are to a large extent attributable to colonialism, and only to a lesser extent to the arrival of Islam. The article also questions existing theories regarding a pre-Islamic Malay manuscript tradition and argues that the emergence of a paper-based Malay manuscript tradition is intrinsically linked to the availability of European paper.